Interactions Between Able-Bodied and Disabled Pupils in Inclusive Public Elementary School in Togo - Rita Kadanga; Boussanlègue Tchable (Unib Press, 2023)
The aim of this research was to examine the interactions between teachers and pupils with disabilities in an inclusive school environment in Togo's public elementary school (EPP). The field survey covered 20 EPPs through 27 observations of inclusive classrooms and over a hundred interviews with teachers and children with disabilities (CWD). The field data show that relations between the two categories of pupils are cordial, given that able-bodied children do not mind sitting on the same bench in class, playing or eating with their disabled classmates.